The single European electricity market: A long road to convergence - François Coppens; David Vivet (National Bank of Belgium, 2006)
In the context of a first Working Paper the authors argued that electricity has a number of characteristics that set it apart from other commodities. It was demonstrated that some of these characteristics might complicate the deregulation process. This paper analyses the ongoing deregulation process in the European electricity sector and attempts to establish whether these difficulties can more readily be solved at European level. It would appear that some problems, e.g. economies of scale in electricity generation, have less of an impact at European level than within smaller national markets. However, a number of difficulties have to be overcome before a unified European electricity market can become a reality. These include the limited interconnection capacities between Member States. The European Commission has taken steps to improve the situation, for example by offering financial support for investments and promoting the development of regional markets as an interim measure ultimately leading to a fully integrated market. Apart from the difficulties related to electricity generation and transmission there are also exogenous factors that influence the ongoing deregulation process, e.g. the implementation of the Kyoto protocol and the dramatic increases in primary fuel prices. This paper argues that a consistent, stable and uniform European regulatory framework must be put in place if the impact of these difficulties is to be minimised.
Keywords: L94; 330; Electricity deregulation; Elektrizitätswirtschaft; Deregulierung; EU-Staaten